Legal Liability for Data Falsification by Third-Party Environmental Service Providers: A Study Centered on Data-Chain Governance and the Reconstruction of Causation - Zhu, Jilun (International Journal of Social Sciences and Public Administration, 2026)
This is because third-party environmental service providers undertake environmental monitoring, environmental impact assessment (EIA), automatic monitoring operation and maintenance, vehicle emission testing, and carbon-emission verification. Practically, however, the falsification of data does not always occur in the form of a simple report, which would be considered outright false. It is disseminated over sampling, analysis, transmission, signing and other nodes, and it comes in the nature of chain and technical forms. Current law already has administrative, civil, and criminal layers of liability, but each layer runs into difficulty in use. Administrative penalties do not easily pierce affiliation and re-entrustment structures. In criminal cases, chain-like division of labor weakens proof of intent. Civil joint liability under Article 65 of the Environmental Protection Law has for a long time been constrained by the difficulty of proving causation. Using typical criminal and administrative cases released in 2023 and 2024, and empirical studies in air monitoring, water monitoring, and carbon-emission reporting, this article focuses on the causation problem in the application of Article 65. The article argues that Chinese law does not need a new concept of causation here. Within the existing framework of adequate causation, different presumptions should be set for different kinds of third-party services, namely continuous discharge-monitoring operation and maintenance, one-time testing and certification, and EIA and carbon-emission verification. This should be supported by statutory duties to keep audit logs and by adverse-inference rules when such logs are missing.